Regional Language Corpus as a Learning Material in Elementary Schools - Викторовна Яковлева, Татьяна; Владимировна Демичева, Вера; Ивановна Еременко, Ольга (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
The work contains theoretical and practical corpus needed for the organization and delivery of the extracurricular classes of Russian in primary schools as well as the instruction for its use. The paper argues for the importance of extracurricular activities and the need for this type of research. The object of the research is extracurricular activity, while the subject is the use of regional linguistic corpus. The paper provides the description of the activities during which children are introduced to the dialectal and regional linguistic characteristics of the Russian language. The authors also analyze the methodological aspects of the linguistics geography. Moreover, the program of the extracurricular activities is presented along with the examples from students’ work with special attention paid to methodological organization of the activities. Finally, this study has practical implications for teachers and lecturers as well for students.